Investigation of the tensile state of the mandible with implants - Авербух, Иосиф; Павленко, Алексей Владимирович; Долгов, Николай Анатольевич; Павленко, Максим Алексеевич; Сиренко, Александра Федоровна (Actual Dentistry, 2019)
Actuality. The absence of teeth leads to functional changes in the maxillofacial system. Rehabilitation of patients is an urgent and still unresolved problem. Objective: to perform a comparative analysis of the tensile state of the mandible with two prosthesis supports on four implants with and without splinting; to investigate the peculiarities of stress distribution in the area of contact of the implant with bone and different angle of implant abutment. Methods. Finite element method and determination of tensile state of the mandible with implants were performed using the ANSYS software package. The Mises equivalent stress distribution in the dental system was used as a criterion for analyzing the results. A number of 3D models of the mandible bone with four implants (with different angles of the abutment axis for lateral (molar) implants) have been developed. Results. With a vertical load of 100 N and a horizontal load of 50 N, which corresponds to the chewing of hard food, maximum stresses occurred in the range from 33.5 to 70.2 MPa depending on load distribution, implant shape and splint presence or absence. In the investigated models with an angle of entry of 45° of the implant into the bone, the maximum stresses did not exceed the maximum permissible values, but at the installation of the splint decreased from 70.2 to 67.8 MPa (when loaded on the lateral implant) and from 33.7 to 33.5 MPa (when loaded on the front implant). When installing a tire for implants with a 0° angle, the tension increased from 66.8 to 68.4 MPa (when loaded on the lateral implant) and decreased from 37.3 to 37.0 MPa (when loaded on the anterior implant). Conclusions. Conducted research testify the significant influence of the implant shape on the stress state of the dental system. The established patterns extend the possibilities of implantation and increase its efficiency by choosing the angle of inclination of the implant abutment. Key words: implant, splint, prosthesis, stress state, mandible.